2018
DOI: 10.1097/md.0000000000011387
|View full text |Cite
|
Sign up to set email alerts
|

Association between density of tumor-infiltrating lymphocytes and prognoses of patients with gastric cancer

Abstract: Introduction:Tumor-infiltrating lymphocytes (TILs) have been shown to be of prognostic significance in patients with gastric cancer. This study aims to investigate the association between density of TILs and prognoses of patients with gastric cancer.Methods:The relative studies of tumor-infiltrating lymphocytes in tumor tissue from patients with gastric cancer were systematically searched from PubMed and Embase until October 31, 2017. The pooled hazard ratios (HRs) and their 95% confidence intervals (95%CI) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
4
30
1
2
Order By: Relevance
“…First, we obtained 245 up-regulated genes and 103 down-regulated genes by analysing the differences between high-and low-score group samples. Following functional enrichment analysis of the up-and down-regulated genes, it was found that many genes are associated with the TME, which is consistent with previous studies reporting the important roles of immune cells and stromal cells in the TME [38][39][40][41]. A total of 10 core genes were extracted from the PPI network, and a module analysis was performed.…”
Section: Discussionsupporting
confidence: 82%
“…First, we obtained 245 up-regulated genes and 103 down-regulated genes by analysing the differences between high-and low-score group samples. Following functional enrichment analysis of the up-and down-regulated genes, it was found that many genes are associated with the TME, which is consistent with previous studies reporting the important roles of immune cells and stromal cells in the TME [38][39][40][41]. A total of 10 core genes were extracted from the PPI network, and a module analysis was performed.…”
Section: Discussionsupporting
confidence: 82%
“…In a meta-analysis, Yu et al stated that TILs are prognostic markers for OS in patients with GC. Moreover, they revealed that intratumoral CD8+ and CD3+ lymphocyte density were associated with good prognosis in GC, whereas CD4+ and FOXP3+ lymphocyte density had no significant effect on survival outcomes [34]. In the present study, both OS and DFS times were significantly higher in patients with high CD8+ TILs density than those with low TILs density.…”
Section: Discussioncontrasting
confidence: 39%
“…The satisfied response might rely on that EBVaGC expresses high levels of PD-L1 [165,170] and exhibits more tumor infiltrating lymphocytes (TILs) [163,167,171,172]. The amount of TILs has been reported to be associated with improved overall survival in GC patients [173]. In a research of advanced GC patients treated with nivolumab, only 25% of patients (1/4) demonstrated good response, and this might be because not all EBVpositive tumors show high PD-L1 expression [174].…”
Section: Ebermentioning
confidence: 99%